First Record and Phylogenetic Significance of a Jurassic Diadematacean Sea Urchin from California. (May 2014) - Mooi, Rich; Hilton, Richard P.
Abstract : Although diadematacean sea urchins (diadematids, aspidodiadematids, and micropygids) likely diverged sometime during the Jurassic, the lack of fossils representing this group has greatly hampered progress in understanding their evolution. No unequivocal Jurassic diademataceans have been described previously from North America. We describe a new genus and species, Sierradiadema kristini, from a single fossil from the Middle Jurassic (Callovian) Colfax sequence of the Mariposa Formation exposed in the Middle Fork American River drainage of the northern Sierra Nevada, California. The specimen, although not complete, reveals details of the spination and tooth morphology often lacking in Jurassic diademataceans, along with test architecture that yields information concerning the relative timing of important events in the origins of the diadematids in particular. We explore this evolution with a phylogenetic analysis of relevant clades with Jurassic times of divergence, finding not only that Sierradiadema n. gen. is the earliest known member of a clade containing the extant Diadematidae, but that it will stimulate ongoing discussion of the putative Jurassic origins of all the diadematacean groups.